Compact Finite Difference Scheme for the Fourth-Order Fractional Subdiffusion System (Advances in Applied Mathematics and Mechanics, 2014)
In this paper, we study a high-order compact difference scheme for the fourth-order fractional subdiffusion system. We consider the situation in which the unknown function and its first-order derivative are given at the boundary. The scheme is shown to have high order convergence. Numerical examples are given to verify the theoretical results.